Condicionamento da superfície de pinos de fibra de vidro: influência na resistência adesiva após ciclagem mecânica e na resistência à flexão dos pinos - Amaral, Marina (2010)
Aim: To evaluate the bond strength between glass fiber post and intrarradicular dentin or core composite resin after several post surface treatments, and the effect of surface treatments on posts flexural strength. Material and methods: The following post surface treatments were evaluated: G1- no conditioning; G2- cleaning with alcohol (AL); G3- AL + silane application (SIL); G4- Al2O3 + SIL; G5- H2O2 + SIL; G6- HF + SIL; G7- H3PO4 + SIL. Tem double-tapered fiber posts from each evaluated surface treatment were cemented into bovine teeth previously embedded into acrylic resin. After, a standard composite resin cylindrical core was build up. Samples were submitted to mechanical cycling (106 cycles, 4 Hz, 37ºC) and sectioned into 2 mm slices. For root portion the bond strength was measured through push-out test, while core slices were machined into hour-glasses and submitted to microtensile bond strength test. The three point bending test was applied to cylindrical posts from G1, G4, G5, G6 and G7, to flexural strength evaluation. Moreover, two posts from these groups were conditioned for scanning electron microscopy (SEM). One-way analysis of variance followed by Tukey s test were applied to each evaluation (α=0,05). Results: the post surface conditioning had no effect on post retention into root canal (p=0,876), however the microtensile bond strength between post and composite resin was significantly affected (p<0,001), where G3 presented the highest values of bond strength. The flexural strength was also influenced by post surface conditioning, where sandblasting with Al2O3 125 μm significantly decreased the posts strength. The analysis through SEM revealed different patterns of surface s modification after conditioning. Conclusions: (1) post retention into root dentin was not affected by post surface conditioning, bust silane application promotes higher microtensile bond strength between post and composite resin; (2) sandblasting posts surface with Al2O3 125 μm decreased posts flexural strength; and (3) different patterns of surface conditioning were observed under SEM.